The acinar-ductal tango in the pathogenesis of acute pancreatitis. Issue 4 (28th September 2010) - Hegyi, Péter; Pandol, Stephen; Venglovecz, Viktória; Rakonczay, Zoltán
Abstract : There is an unacceptably high mortality in acute pancreatitis, which is due to the lack of specific treatments for the disease. A major reason stated to account for the inability to develop effective treatments is that there are multiple pathobiologic pathways activated in the acinar cell mediating pancreatitis making it difficult to choose molecular targets for therapeutic strategies. However, this reasoning limits opportunities for therapeutic development because it does include another important participant in pancreatitis - the pancreatic duct cells. The most recent advance in pancreatitis research is that depletion of both glycolytic and oxidative ATP synthesis is a common event in both acinar and ductal cells. Although ATP has a very short half-life in the blood and is hydrolysed to ADP, there is clear evidence that encapsulating ATP into liposomes can effectively drive ATP into the cells which can be effective in protecting them from necrosis. In this review, we will examine the effects of different insults associated with pancreatitis on both the acinar and ductal components of the exocrine pancreas pointing out the role of the ductal epithelial responses in both attenuating and increasing the severity of pancreatitis. In addition, we propose that exogenous ATP administration may restore ductal and acinar function providing therapeutic benefit.